2012
DOI: 10.1177/0306624x12458503
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Offending

Abstract: This research focuses on a detailed exploration of late-onset offending. Using the National Youth Survey, this work seeks to answer three questions. First, is late-onset offending a real phenomenon? Second, if late onset does exist, is the evidence for it conditioned by how we define crime and delinquency? Finally, is late-onset offending an artifact of measurement methodology? Most literature evidencing late onset relies on official police contact and arrest data. Propensity or control theories in general pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 89 publications
1
7
1
Order By: Relevance
“…Zara , but in contrast to others (McGee & Farrington, 2010;Wiecko, 2014), our analyses indicate that adult-onset is not a rare event. In our sample, 16% of participants reported offending for the first time after the age of 18.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Zara , but in contrast to others (McGee & Farrington, 2010;Wiecko, 2014), our analyses indicate that adult-onset is not a rare event. In our sample, 16% of participants reported offending for the first time after the age of 18.…”
Section: Discussioncontrasting
confidence: 99%
“…McGee and Farrington (2010) analyzed data from the Cambridge Study in Delinquent Development, a prospective longitudinal study of 411 men from inner-city London followed from age 8 to age 48, and found that all adult-onset offenders (i.e., those who were convicted for the first time at age 21 or later) self-reported offending prior to adulthood that was not, however, sufficiently frequent or serious to warrant a conviction. More recently, Wiecko (2014), using data from the U.S. National Youth Survey, a longitudinal study of delinquency among a sample of 1,725 persons aged 11 to 17, found that all late-onset offenders self-reported delinquency during childhood and adolescence yet they had not been arrested even though their behaviour justified arrest. These findings contradict results by Mata and van Dulmen (2012), who found, using data from the National Longitudinal Study of Adolescent Health in the United States, that 13% of the sample reported offending in adulthood only (although the study by Mata and van Dulmen used trajectory analysis to track changes from low to high levels of antisocial behaviour rather than change from a completely non-criminal to a criminal pathway).…”
mentioning
confidence: 99%
“…The prevalence of AO offenders in this general population survey was 8.4%, exceeding the rates of AL (1.8%) and LP (2.2%) combined. The existence of AO offenders remains controversial in the literature, with some authors viewing AO offending as an artifact of prior offending that has simply gone undetected or not serious to warrant a criminal justice system response (DeLisi & Piquero, 2011; McGee & Farrington, 2010; Wiecko, 2014) or a product of overly strict definitions of adulthood (Sohoni et al, 2014). Recently, DeLisi et al (2018) have argued that the existence of AO offending has been mixed largely due to the narrow focus on early adulthood (Krohn et al, 2013; Sohoni et al, 2014) and is primarily based on official data lacking triangulation with self-report data (Zara & Farrington, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The 14 studies were as follows: Dunedin Multidisciplinary Health and Development Study (Moffitt, Caspi, Harrington, & Milne, 2002), Kauai Longitudinal Study (Werner & Smith, 1992), Montreal Two-Samples Longitudinal Studies (LeBlanc & Frechette, 1989), National Collaborative Perinatal Project (Denno, 1990), Columbia County Study (Dubow, Huesmann, Boxer, & Smith, 2014), Racine Cohort Study (Eggleston & Laub, 2002), Philadelphia Birth Cohort Study (Wolfgang, Thornberry, & Figlio, 1987), Second Philadelphia Birth Cohort Study (Tracy & Kempf-Leonard, 1996), Cambridge-Somerville Study (McCord, 1978), Orebro Project (Bergman & Andershed, 2009), US National Youth Survey (Wiecko, 2012), Canadian Criminal Records Survey (Carrington, Matarazzo, & De Souza, 2005), Stockholm Project Metropolitan (Nilsson & Estrada, 2009), and Jyvaskyla Longitudinal Study of Personality and Social Development (Pulkkinen, Lyyra, & Kokko, 2009). The previous article reports how these studies defined the three offending types.…”
Section: Methodsmentioning
confidence: 99%